Let Her Play: A report on gender-based violence in video games - Mettler, Kirsten (Embodied: The Stanford Undergraduate Journal of Feminist, Gender, and Sexuality Studies, 2022)
Globally, video games are a $152 billion industry, and approximately 3.1 billion people, or 40% of the population, are players (Ingersoll & Anti-Defamation League, 2019, Price, 2020). Gaming is a huge industry, and it’s only getting bigger. Unfortunately, women and other historically marginalized groups often face staggering levels of harassment and violence in these communities. This report aims to explore the issue of gender-based violence in video games by analyzing contributing factors and proposing gaming company interventions.
Number: 1
Keywords: Bibliographie; Irina; Nettoyer; esports

Review: Cooperative Gaming: Diversity in the Games Industry and How to Cultivate Inclusion - Hanussek, Benjamin (Press Start, 2022)
Review: Cooperative Gaming: Diversity in the Games Industry and How to Cultivate Inclusion, by Alayna Cole and Jessica Zammit. 2020. CRC Press. xv + 95 pp.
Number: 2
Keywords: Irina; diversity; game industry; game studies; inclusion

Exploring Vicarious Liability to Remedy the #E-Too Movement - Hewson, Eloise (York Law Review, 2022)
The esports, or competitive video gaming, industry is an exciting area of economic and cultural growth. Gaming can facilitate interpersonal connection, shared problem-solving, and creativity. Players may purchase a game, watch a streamer play it online, join an online gaming community, attend a tournament, compete professionally, or find employment in game development or a related field. The gaming industry generates enormous economic value and employs tens of thousands of people in the UK alone. However, the esports sector does not extend its benefits equally. Women are regularly verbally harassed in video games, countless women have been groped at esports events, women have been raped by professional players, underage fans have been groomed. Abuse is endemic to online gaming communities.
Keywords: Bibliographie; Irina; Nettoyer

Designing Women: Learning from Feminist Legacies and the Women-In-Games Movement - Schoemann, Sarah (Georgia Institute of Technology, 2021)
In 2019 the video games industry was rocked by a slew of high-profile sexual harassment and assault allegations that some called the #MeToo movement of the games world, but to many these revelations came as no surprise. From the 2004 EA Spouse controversy to the 2014 #Gamergate harassment campaign the games industry has long been known for harboring an at times toxic atmosphere of exploitation and discrimination. This project looks at a handful of Women-In-Games organizations that set out to change the experience of women in the industry by helping newcomers to gain high tech skills and to supporting early career professionals through mentorship and community building. Along the way, it combines the study of these Women-In-Games organizations with a years-long collaboration bringing video games to the US' oldest feminist bookstore, Charis Books & More in Atlanta, GA. Through examining the work and values of two types of organizations devoted to women's equality, one a historic feminist movement-building space and the others, contemporary interventions into the professional games and tech industry, this study asks the questions "What can the Women-In-Games movement learn from the rich history of feminist organizing at spaces like Charis?" "Can games play a part in feminist movement building?" and "What does the future of feminist organizing look like in the games industry?”
Accepted: 2021-09-15T15:43:41Z Publisher: Georgia Institute of Technology
Keywords: Bibliographie; Irina; Nettoyer

“Frat Boy” Culture: Will the Activision Lawsuit Reform the Gaming Industry? - Lawrence, Kelsey (2021)
Keywords: Irina; games; gaming; industry; lawsuits; sexual harassment; students

A More Pixelated Union: A Look at the Path to Unionization in the Video Game Industry under Trump's National Labor Relations Board - Selfridge, William C. (2021)
Keywords: Irina

Title IX, Esports, and #EToo - Stoever, Jane K (The George Washington Law Review, 2021)
As colleges and universities increasingly award video gaming scholarships, field competitive esports teams, construct esports arenas in the centers of campuses, and promote student interaction through gaming, schools should anticipate the sexual cyberviolence, harassment, and technology-enabled abuse that commonly occur through gaming.
Keywords: Bibliographie; Irina; Nettoyer

Cooperative Gaming: Diversity in the Games Industry and How to Cultivate Inclusion - Cole, Alayna; Zammit, Jessica (CRC Press, 2020)
Description Cooperative Gaming provides context and practical advice regarding diversity in the games industry. The book begins with a deep dive into research literature and the history of diversity in the games industry to provide context around what diversity is and why it is a topic worth considering. The book looks at the different facets of diversity and games, exploring the issues and solutions within game development, studio management, event planning, and more. It provides people with practical advice about being a marginalized person in the games industry and how to be heard, how studios can support inclusive practices, and events can actively become more accessible to a diverse audience. Key Features • Explores the history of diversity in games • Provides important information around what it is like to be a marginalized person in the industry • Gives practical steps to improve the inclusivity of the industry that are designed to aid in contextualizing and upskilling new developers Author Bios Alayna Cole is the managing director of Queerly Represent Me, a not-for-profit championing queer representation in games. Alayna is also a producer at Sledgehammer Games, co-chair of the IGDA LGBTQ+ special interest group, and an award-winning games journalist and game developer. She was featured on the 2016 and 2017 Develop Pacific 30 Under 30 lists and the 2017 and 2019 Develop Pacific Women in Games lists, and she has received several other accolades in the industry. Jessica Zammit started writing in 2013 for Start Select Media, and for the next five years she followed her interest in writing about representations of mental health, diversity, and particularly, sexuality in video games. Jessica has been speaking about diversity in games at conventions such as PAX Australia since 2016 and has been featured on several other discussions in and around the topic of representation in games and games criticism. Along with her co-author, she is co-chair of the IGDA LGBTQ+ special interest group, and she was featured on the 2018 Develop Pacific 30 Under 30 and Women in Games lists.
Google-Books-ID: 0XjtDwAAQBAJ
Keywords: Computers / Programming / Games; Irina

Video Games - Pletcher, Isaac (Communication Technology Update and Fundamentals, 2020)
A video game is an interactive digital entertainment that you “play” on some type of electronic device. The medium has existed in some form since the 1950s, and since that time, has become a major worldwide industry, spawning technology battles and being birthed in new iterations that become ubiquitous parts of modern life. This chapter will look at the development of video games from the beginning, through the golden age, and into the era of the console wars. Further, it will point out the enormous revenues video games make, and show how the #metoo movement and unions are working to change the face of the industry.
Num Pages: 12
Keywords: Irina

Gendered Barriers In The Gaming Industry - Singh, Tanya (Journal of Sports Law, Policy and Governance, 2020)
As of 2019, there are an estimated 2.5 billion garners globally. Roughly half of all garners are female. Despite the figures, there is a serious underrepresentation of female gainers in the professional gaming and game development community. It is thus important to examine the underlying causes hindering equally capable female gainers and game developers from pursuing a serious career in gaming, at par with their male counterparts.In this article, the authorexamines the impact of the culturalassociationof games with the male demography, stereotypes andstructuralbarrierslimiting women from realizing theirfullpotential, female representation in video games and workplace, pervasive misogyny and sexual harassment of women across all levels in the industry, and lastly, the steps that can be taken to better the status quo in favour of women.
Keywords: Bibliographie; Irina; Nettoyer

Speaking in Public: What Women Say about Working in the Video Game Industry - De Castell, Suzanne; Skardzius, Karen (Television & New Media, 2019)
Since the 1990s, conversations about the dearth of women working in the video game industry have centered on three topics: (1) ways to draw more women into the field, (2) the experiences of women working in the industry, and (3) the experiences of those who once worked in the industry but left. Although there has been considerable research on the conditions and occupational identities of video game developers, less scholarly attention has been devoted to women in gameswork, the barriers/obstacles and challenges/opportunities they face, and how they talk about their experiences. This article offers a feminist approach that demonstrates how discourse focused on affect can be reread as intimately related to silences about power and how the rhetorical constraints that public speech imposes upon what can be said about “women in games” aid us in understanding what might remain unspoken, and why.
Keywords: Bibliographie; Irina; Nettoyer